2003
DOI: 10.1016/s0092-8674(03)00422-7
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Cells Induce Migration of Phagocytes via Caspase-3-Mediated Release of a Lipid Attraction Signal

Abstract: Efficient engulfment of the intact cell corpse is a critical end point of apoptosis, required to prevent secondary necrosis and inflammation. The presentation of "eat-me" signals on the dying cell is an important part of this process of recognition and engulfment by professional phagocytes. Here, we present evidence that apoptotic cells secrete chemotactic factor(s) that stimulate the attraction of monocytic cells and primary macrophages. The activation of caspase-3 in the apoptotic cell was found to be requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
684
1
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 846 publications
(713 citation statements)
references
References 34 publications
19
684
1
9
Order By: Relevance
“…One of the first identified recruitment signals for apoptotic cell engulfment was lysophosphatidylcholine (LPC). 23 Lauber et. al.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
See 2 more Smart Citations
“…One of the first identified recruitment signals for apoptotic cell engulfment was lysophosphatidylcholine (LPC). 23 Lauber et. al.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
“…al. 23 showed that the cell supernatants taken from apoptotic MCF7 cells could induce phagocyte migration. The authors linked soluble LPC as the factor responsible for recruitment.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, whereas the caspase-3-mediated cleavages of a-fodrin, gelsolin, rho-associated kinase-1 (ROCK-1) and p21-activated kinase 2 (PAK2) contribute to membrane blebbing, cleavage of the inhibitor of the caspase-activated DNase (ICAD) leads to the typical DNA fragmentation pattern observed in apoptosis [1]. Furthermore, with the cleavagemediated activation of the calcium-independent phospholipase A2 and subsequent production of the chemotactic phospholipid lysophosphatidylcholine, caspase-3 appears to be also responsible for the generation of so-called ''eatme'' signals that induce migration of phagocytes to the site of apoptotic cell death [6]. Thus, caspase-3 not only instigates and pursues the demise of a cell, but, in addition, makes sure that the corpse is properly disposed, a function crucial for avoiding inflammatory processes.…”
mentioning
confidence: 99%
“…From a more general point of view, phospholipids (and, in particular, their oxidatively modified counterparts) appear to have assumed several key roles in apoptosis, at least in mammalian cells, including the cardiolipin-dependent release of proapoptotic factors from mitochondria, 34 and the lysophosphatidylcholine-triggered chemoattraction of macrophages to sites of apoptotic lesions. 35 Further studies in the field of oxidative lipidomics of apoptosis are expected to shed more light on the manifold roles of these ubiquitous cellular signaling molecules.…”
Section: Post Scriptummentioning
confidence: 99%